LEBESGUE’S CRITERION FOR INTEGRABILITY - Bayu Riyadhus Saputro; Sumaji . (EDUPEDIA, 2018)
Lebesgue integral was defined constructively by using outer measure, measurable set, measurable function and Lebesgue measure concept. Then it was constructed by using simple function. The requirement of a Lebesgue integrable function to be Riemann integrable is bounded function and the set of discontinuities of that function has measure zero.